2002
DOI: 10.1248/cpb.50.749
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid Deformable Vesicles for Buccal Delivery of Insulin.

Abstract: To investigate the possibility of the enhancing effect of deformable vesicles on buccal delivery of insulin, two kinds of vesicles with and without the presence of sodium deoxycholate (deformable vesicles and conventional vesicles) were prepared by reverse phase evaporation methods. The liposomal entrapment efficiency was determined by column chromatography. The particle size and morphology of the vesicles were also evaluated. The hypoglycemic effects, insulin concentrations, and residual amounts of insulin de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…1 The delivery of insulin by nonparenteral routes has gained significant attention over last 2 decades. The alternate routes explored are ocular, 2,3 nasal, 4 buccal, 5,6 rectal, 7 pulmonary, 8,9 and oral. 10,11 Among all of the alternative routes of administration of insulin, the oral route offers the maximum advantage in terms of patient compliance.…”
Section: Introductionmentioning
confidence: 99%
“…1 The delivery of insulin by nonparenteral routes has gained significant attention over last 2 decades. The alternate routes explored are ocular, 2,3 nasal, 4 buccal, 5,6 rectal, 7 pulmonary, 8,9 and oral. 10,11 Among all of the alternative routes of administration of insulin, the oral route offers the maximum advantage in terms of patient compliance.…”
Section: Introductionmentioning
confidence: 99%
“…Comparative result showed that subcutaneous administration of insulin solution, the relative pharmacological bioavailability and the relative bioavailability in the insulin-deformable vesicles group were 15.59% and 19.78%, respectively, which were higher than in the conventional insulin vesicles (P < 0.05), blank deformable vesicles and insulin mixture groups (P < 0.05). [141] However, Cornparisons calculated at each period PF-127 gel without fatty acid versus PF-127 gel containing oleic acid, EPA or DHA (*P < 0.01). [139] the effect of salivary scavenging and accidental swallowing of delivery system; barrier property of buccal mucosa stands as the major limitations in the development of buccal adhesive drug delivery systems.…”
Section: Buccal Insulinmentioning
confidence: 99%
“…A novel type of highly deformable lipid vesicle (transferosome), composed of soybean phosphatidylcholine, cholesterol and sodium deoxycholate, has been developed in recent years to enhance insulin bioavailability [24]. Compared with the subcutaneous administration of insulin solution, the relative pharmacological bioavailability in the insulin-deformable vesicles group was 15.59% and 19.78%, respectively, which was higher than in the conventional insulin vesicles, blank deformable vesicles and insulin mixture groups.…”
Section: Enzyme Inhibitorsmentioning
confidence: 99%